IMPLEMENTASI ZAKAT PRODUKTIF DALAM PEMBERDAYAAN EKONOMI BERBASIS PENTAHELIX PADA BAZNAS KABUPATEN PEKALONGAN - Adimas Faturrokhman (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
This study examines the implementation of productive zakat in economic empowerment based on the pentahelix approach at Baznas Pekalongan Regency. The academic concern underlying this research arises from the persistent level of poverty and the dominance of micro-enterprises that face structural limitations in capital, managerial capacity, and market access, despite the existence of productive zakat programs. This study aims to analyze how productive zakat is implemented, to explore the roles of pentahelix actors???government, academics, business sector, community, and media???and to assess the impact of the program on mustahik economic empowerment. This research employs a qualitative approach with descriptive-analytical methods. Data were collected through in-depth interviews, observations, and documentation involving Baznas managers, relevant stakeholders, and beneficiaries of productive zakat programs. Secondary data were obtained from official Baznas documents, reports, and publications from Statistics Indonesia. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that productive zakat implemented by Baznas Pekalongan Regency contributes positively to strengthening mustahik business capacity and economic resilience, particularly for beneficiaries who already operate micro-enterprises. However, the pentahelix-based collaboration has not yet been fully integrated and institutionalized. Baznas remains the dominant actor, while the roles of other stakeholders are still supportive and sporadic. The effectiveness of productive zakat is strongly influenced by the intensity of business mentoring and the availability of a supportive empowerment ecosystem. This study contributes to the development of Islamic economic literature by integrating productive zakat management with a pentahelix framework at the local level and provides practical recommendations for strengthening collaborative and sustainable zakat-based empowerment programs.